Choosing to Prosecute: Expressive Selection at the International Criminal Court - DeGuzman, Margaret M. (2012)
The International Criminal Court (ICC), an institution in its infancy, has had occasion to make only a relatively small number of decisions about which defendants and which crimes to prosecute. But virtually every choice it has made has been attacked: the first defendant, Thomas Lubanga, was not senior enough and the crimes with which he was charged-war crimes involving the use of child soldiers-were not serious enough; the Court should have investigated British soldiers for war crimes committed in Iraq; the ICC should not be prosecuting only rebel perpetrators in Uganda and the Democratic Republic of Congo; the Court's focus on situations in Africa is inappropriate; the Court has focused insufficient attention on gender crimes; and so on. Much of the debate about such selection decisions centers on whether the ICC, and particularly its prosecutor, are improperly motivated by political considerations. Critics charge that selection decisions are inappropriately political, while the Court's current prosecutor, Luis Moreno-Ocampo, counters that his decisions are apolitical-that he is simply implementing the law enunciated in the ICC's statute. Most recently, some authors have suggested that the prosecutor's role is inevitably political and should be acknowledged as such. The participants in this debate rarely define what they mean by political, nor will this Article attempt such definition. Instead, this Article seeks to reframe the debate about the ICC's selection decisions by shifting from the current focus on the boundaries between legal and political criteria to a constructive dialogue about the most appropriate goals and priorities for the Court. The ICC's core selectivity problem is that the Court lacks sufficiently clear goals and priorities to justify its decisions. States created the ICC to adjudicate the most serious crimes of concern to the international community as a whole, but they gave it a budget that enables only a handful of prosecutions per year. Persons charged with implementing the Court's broad mandate-its prosecutor and judges-must thus select a few cases from among thousands. Yet the international community has provided the Court virtually no guidance about what goals it should seek to achieve through the cases it selects, beyond the vague mandate to strive to end impunity for the most serious crimes